Effect of the Stirrup Shear Reinforcement on the Dynamic Behavior and Failure Modes of Two-Way Reinforced Concrete Slab Subjected to the Low-Velocity Impact Loading - Al-Dala’ien, Rayeh Nasr; Syamsir, Agusril; Abu Bakar, Mohd Supian; Usman, Fathoni; Abdullah, Mohammed Jalal (Arabian journal for science and engineering (2011), 2024)
Reinforced concrete slabs can be exposed to explosive and impact loads, prompting extensive research into their behavior under various static and dynamic loading conditions. Researchers have explored numerous techniques to enhance the structural integrity of these slabs when subjected to impact loads, but certain knowledge gaps persist. Particularly, the application of shear reinforcement, such as conventional stirrup shear reinforcement, to strengthen slabs against impact remains relatively uncommon. This study aimed to investigate the impact of conventional stirrup shear reinforcement on the dynamic response and failure modes of reinforced concrete slabs when subjected to low-velocity impact loading. The first phase involved experimental evaluation, focusing on the influence of vertical conventional stirrups as shear reinforcement in two-way, fully fixed RC slabs. Portable drop weight testing equipment was used to subject six (800 × 800 × 90 mm) RC slabs, to impact testing. Three slabs were strengthened with stirrups in two directions orthogonally configuration, while three control slabs received no additional reinforcement. Various parameters, including vertical displacement, strain at multiple points on the stirrups, main steel, and concrete, as well as acceleration at a specific point on the slab, were measured. Additionally, the failure modes were closely monitored. In the second phase, finite element models of the slab study samples were created using ABAQUS software. The numerical model results aligned with the experimental findings, indicating that the proposed finite element model can effectively assess the structural behavior of reinforced concrete slabs subjected to low-velocity impact loads. The third part of the research involved a parametric study to investigate the effects of bar diameter and drop position on the structural response of the slabs. The outcomes of this study highlight the significant positive impact of shear reinforcement, particularly in the form of conventional stirrups, on the load-bearing capacity of reinforced concrete slabs. Slabs with stirrups exhibited noteworthy improvements in strength, stiffness, and ductility compared to control specimens without shear reinforcement. Specifically, the presence of conventional vertical stirrup shear reinforcement increased the slab's capacity by 29.5% under the total impact energy until complete failure.